Elementary statistical quality control - Burr, John T. (Marcel Dekker, 2005)
Maintaining the reader-friendly features of its popular predecessor, this second edition illustrates fundamental principles and practices in statistical quality control for improved quality, reliability, and productivity in the management of production processes and industrial and business operations. Presenting the key concepts of statistical quality control in a simple and straightforward manner, this reference provides a solid foundation in statistical quality control theory and applications. Reflecting upon classic examples and case studies and recent industrial data, this resource explores how to develop solutions to real-world dilemmas in the manufacturing and service industries.